Hematologic variables of the Arrau turtle (Podocnemis expansa) under the effects of different anticoagulants and cytologic stains - Garcia, Guilherme C. (2021)
Background: The hematology of turtles of the Amazon, such as the Arrau turtle (Podocnemis expansa), has not been well described in the literature. Referencing how to collect and analyze blood samples is fundamental for the medical practice of these exotic animals. Objectives: The aim of this study was to evaluate the hematologic parameters of Arrau turtles of the Amazon to determine the best anticoagulant (EDTA, citrate, or sodium heparin) and cytologic stain (Giemsa, Quick Panoptic, or Rosenfeld) for use with this species. Methods: Blood samples from eight turtles were collected. Three blood smears were made using blood without anticoagulant, and the rest of the sample was distributed in three tubes, containing EDTA, citrate, and sodium heparin, for erythrogram and leukogram analyses. Results: All blood samples anticoagulated with EDTA showed marked hemolysis. Blood collected with citrate showed minimal hemolysis, and blood collected with sodium heparin did not have any hemolysis. Some analyses were not performed on blood containing EDTA because of the intense hemolysis. The erythrocyte variables were obtained and showed better results for blood samples in heparin. Blood smears without anticoagulant were appropriate for differential leukocyte counts with the three stain types, while blood with any of the anticoagulants made it difficult to differentiate leukocytes. Conclusions: Sodium heparin showed the best results and should be the anticoagulant of choice for hematologic studies in P expansa. All cytologic stains were efficient, allowing adequate identification of distinct cell groups. Leukocyte differentiation was assured and had better contrast using blood smears made from blood without an anticoagulant.